Assessment of Morphological Characteristics of Kuchi Indigenous Chicken Ecotype of Kenya - Ben K. , Chesoo; George , Oduho, W.; David , Kios, K.; H A. , Rachuonyo; J.K , Kitilit, (African Journal of Education,Science and Technology (AJEST), 2016)
Kenya has a rich diversity of Indigenous Chicken (IC).One of them is the Kuchi ecotype whose phenotypic attributes have made it popular in terms of high mature body weight. However, characterization on the phenotypic traits of this chicken ecotype has not been adequately studied. Thus, this study was carried out to assess the morphological characteristics, namely: Feather Colours, Comb Type, Shank Colours and the Meat yield (Killing Out percentage-KO %) of Kuchi IC ecotype kept under a Scavenge System with Supplementation (SSS) from week 17 to 30 of age. The experimental birds were derived from randomly collected pure Kuchi eggs which were bought, hatched artificially and managed intensively using commercial chick and growers mash from day old to 17weeks.From 18 weeks of age, 18 chickens were subjected to a scavenge feeding with cafeteria supplementary ration of commercial layers mash for a period of 12 weeks. The experiment was executed at week 30, involving descriptive statistics and visual appraisals. Generated data was analyzed using an Excel (2007) Soft ware tool. Results revealed three categories for Feather colours: Solid–One, Mixed-Two and Heterogeneity (several-including Frizzled) as: 27.8%, 33.4% and 39%, respectively. Frizzled trait constituted 11.2%. Comb types of Kuchi were categorized into three phenotypic characteristics: Pea (55.6%, Single (22.2%) and Rose (22.2%) types. Shank colours fell into two categories: Yellow (77.8%) and White (22.2%).Kuchi at 30weeks of age had a KO % of 67.8% and 65.9%, for cock and hen respectively. This indicates that a Kuchi cock at 30 weeks old is heavier by 1.9KO%, than a hen of same age. Results from this study can be utilized during selection and breeding of Kuchi and in determining correlations of traits of economic importance in other IC ecotypes.